Combretum leprosum Mart.: Botany, Ethnomedicinal Uses, Biological Activities, Phytochemistry and Conservation Needs (Research, Society and Development, 2022)
Combretum leprosum is a plant species with wide distribution in Brazil known as “mofumbo”, standing out in studies associated with its pharmacological and ethnobotanical activity. The medicinal applications of the species are widely reported in the literature, using the bark, leaves and flowers as healing agents. Given the economic, pharmacological and ecological importance, this work aimed to present a systematic review of production, conservation status and knowledge about the species in different fields of knowledge. The literature review was based on seven categories, characterized according to the study area: biological and/or pharmacological activity (32 articles), importance of conservation status (29), botanical aspects (18), phytochemistry (9), geographic distribution (8), foraging (5) and ethnobotanical uses (2). Most of the works address biological and/or pharmacological activity of the species, and its application is focused on antitumor action, treatment against Chagas disease, antinociceptive behavior, antibacterial, antioxidant, anti-inflammatory and antiproliferative action. Among the compounds isolated from C. leprosum with different applications, 3β-6β-16β-trihydroxylup-20(29)-ene stands out, a lupane triterpene isolated from different parts of the plant, associated with different medicinal and therapeutic applications. The species was highlighted in works associated with environmental regeneration, being resistant to different phytophysiognomies and showing tolerance to environments contaminated by heavy metals, being able to represent an important species in reforestation programs and recovery of degraded environments. However, even with the growing number of studies associated with C. leprosum in recent years, the species does not have an assessment regarding its degree of threat, demonstrating the need for research associated with the species and the possible impacts that its representatives may suffer, helping in sustainable development and conservation programs.